2019
DOI: 10.1097/md.0000000000015251
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of long non-coding RNA ZEB1-AS1 in Chinese cancer patients

Abstract: Background:Aberrant expression of long non-coding RNA Zinc finger E-box binding homeobox 1 antisense 1 (lncRNA ZEB1-AS1) can be detected in numerous malignancies. Therefore, a meta-analysis had been carried out in this study, aiming to examine the prognostic value of lncRNA ZEB1-AS1 in malignancies.Methods:Electronic databases, such as PubMed, OVID as well as Web of Science, had been systemically retrieved from inception to February 14th, 2019. Besides, the hazard ratios (HRs), together with the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In the current study, ZEB1-AS1 functioned as a regulator of ZEB1 The data from meta-analysis revealed that high ZEB1-AS1 level was closely correlated with overall survival (HR = 2.16, 95% CI: 1.89-2.47), poor histological grade, high tumour staging and lymph node metastasis among patients with cancer, 36 which was similar with previous report. 37 These findings indicate that suppression of ZEB1-AS1 expression may be a potential strategy for therapy of many tumour patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, ZEB1-AS1 functioned as a regulator of ZEB1 The data from meta-analysis revealed that high ZEB1-AS1 level was closely correlated with overall survival (HR = 2.16, 95% CI: 1.89-2.47), poor histological grade, high tumour staging and lymph node metastasis among patients with cancer, 36 which was similar with previous report. 37 These findings indicate that suppression of ZEB1-AS1 expression may be a potential strategy for therapy of many tumour patients.…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, the precise metastasis mechanism in cancer patients is still unclear, even though metastasis will predict dismal prognosis [29,30]. Currently, identifying novel molecular markers is necessary, so as to estimate tumor metastasis, because these markers have crucial parts in cancer treatment and prediction [31]. LncRNAs are one of these molecular markers, which are able to impact the development as well as occurrence of tumor; in addition, they have also been shown to display the potential of easy collection of useful biomarkers to monitor and diagnose tumors [32].…”
Section: Discussionmentioning
confidence: 99%